2010
DOI: 10.1364/ol.35.003589
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort pulse compression and delivery in a hollow-core photonic crystal fiber at 540 nm wavelength

Abstract: We have fabricated a bandgap-guiding hollow-core photonic crystal fiber (PCF) capable of transmitting and compressing ultrashort pulses in the green spectral region around 532 nm. When propagating subpicosecond pulses through 1 m of this fiber, we have observed soliton-effect temporal compression by up to a factor of 3 to around 100 fs. This reduces the wavelength at which soliton effects have been observed in hollow-core PCF by over 200 nm. We have used the pulses delivered at the output of the fiber to machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…HCFs can be broadly divided into hollow core photonic bandgap fibers [1,2] and hollow core leaky mode fibers depending on the optical properties of the cladding structure. HCFs provide a new playground for study of light-gas interaction [3] and have many applications where the fiber material properties would usually become a limiting factor, such as in high power laser pulse delivery [4], mid-infrared and farinfrared wavelength transmission [5,6], ultrafast laser pulse transmission [7] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…HCFs can be broadly divided into hollow core photonic bandgap fibers [1,2] and hollow core leaky mode fibers depending on the optical properties of the cladding structure. HCFs provide a new playground for study of light-gas interaction [3] and have many applications where the fiber material properties would usually become a limiting factor, such as in high power laser pulse delivery [4], mid-infrared and farinfrared wavelength transmission [5,6], ultrafast laser pulse transmission [7] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, Wheeler et al demonstrated that Kagome HC-PCF could be spliced with comparable splice loss to that of PBG guiding ones, provided the HC-PCF is tapered [43] . Bandgap HC-PCF also finds applications in soliton generation [14] and pulse compression [44] . As a host for light-matter interactions [16,17] , which is one of the most advanced applications of HC-PCF, bandgap HC-PCF can enhance the interaction intensity by up to a millionfold because of its small core size and low optical attenuation.…”
Section: Comparisonmentioning
confidence: 99%
“…The best-reported loss figure in PBG HC-PCF guiding, in this visible wavelength range, is 0.87 dB∕m at 557 nm [8]. This is limited by the combination of a large core-cladding mode optical overlap (>1%), and by surface roughness at the silica core-surround [9].…”
mentioning
confidence: 91%